From Ischemic Conditioning to 'Hyperconditioning': Clinical Phenomenon and Basic Science Opportunity. Issue 4 (1st October 2014) - Whittaker, Peter; Przyklenk, Karin
Thousands of articles have been published on the topic of ischemic conditioning. Nevertheless, relatively little attention has been given to assessment of conditioning's dose-response characteristics. Specifically, the consequences of multiple conditioning episodes, what we will term "hyperconditioning", have seldom been examined. We propose that hyperconditioning warrants investigation because it; (1) may be of clinical importance, (2) could provide insight into conditioning mechanisms, and (3) might result in development of novel models of human disease. The prevalence of angina pectoris and intermittent claudication is sufficiently high and the potential for daily ischemia-reperfusion episodes sufficiently large that hyperconditioning is a clinically relevant phenomenon. In basic science, attenuation of conditioning-mediated infarct size reduction found in some studies after hyperconditioning offers a possible means to facilitate further discernment of cardioprotective signaling pathways. Moreover, hyperconditioning's impact extends beyond cytoprotection to tissue structural elements. Several studies demonstrate that hyperconditioning produces collagen injury (primarily fiber breakage). Such structural impairment could have adverse clinical consequences; however, in laboratory studies, selective collagen damage could provide the basis for models of cardiac rupture and dilated cardiomyopathy. Accordingly, we propose that hyperconditioning represents the dark, but potentially illuminating, side of ischemic conditioning - a paradigm that merits attention and prospective evaluation.